Adaptación de la escala de identidad para lesbianas, gays y bisexuales (LGBIS) en un grupo de lesbianas, gays y bisexuales del Perú - Vinces Guillén, Jessica Marialaura (2016)
Sexual orientation identity involves private and public ways of self-identification therefore it is considered as a key multidimensional element in the identity of people. Moreover, it has direct influence in making decisions in the personal and interpersonal sphere. Nevertheless, in Peru there is no scale that evaluates this construct in lesbian, gay and bisexual (LGB) people. Therefore, this research aimed to adapt and assess the psychometric properties of the Lesbian, Gay and Bisexual Identity Scale (LGBIS) proposed by Mohr and Kendra (2011) on a sample of 378 LGB Peruvian people. First of all, a linguistic adaptation of the scale was done. Later, appropriate validity evidence based on test content was assessed by 6 experts in the topic. Validity evidence based on internal structure was estimated by an exploratory factor analysis which showed a multidimensional solution of two factors. Consequently, this structure differed from the original version. The two dimensions were identified as: uncertainty and acceptance concerns (ordinal a = .88, EEM = 3.29) and identity integration (ordinal a = .91 EEM = 1.86), According to these results, a new scale was proposed: “The Lesbian, gay and bisexual dimensions of Sexual Orientation Identity Scale” (EDOS-LGB). In conclusion, results showed that interpretations based on the scores obtained by adapting the EDOSLGB presents validity and reliability evidence in lesbian, gay and bisexual people from Perú.